(untitled) (Innovation in Woodworking Industry and Engineering design, 2026)
The present article focuses on the important furniture production and consumption data in the world, Europe and Bulgaria, data about the main exporters in the world and regionally and furniture import. Main conclusions related to world production, consumption, export and import of furniture are drawn. Analysis of the Bulgarian furniture production and the market development have been made. Main trends in furniture market development in the following years globally are given. The information is based on data provided by CSIL (Centre for Industrial Studies, Italy), including official statistical data about the 100 most important countries in the world where the population amount to 6.6 billion, representing 85% of the total population on earth, Eurostat, Bulgarian Chamber of Woodworking and Furniture Industry and the National Statistical Institute.